Fragment einer präparierten und linierten Kalksteintafel mit Auszug aus dem Hymnus auf Amun-Re von pBoulaq 17 (oDeM 1793) - Fischer-Elfert, Hans-W. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The limestone tablet oDeM 1793 is known particularly for its representativeness as a writing medium. In the following it will be shown that the preserved hieratic text can be identified as part of the hymnus of Amun of pBoulaq 17.